Impact of spinal cord anomalies on defecation and quality of life in children with anorectal malformations - FAN Linxiao; FENG Wei; XIANG Chenzhu (陆军军医大学学报)
Objective‍　‍To explore the relationship between postoperative defecation dysfunction and quality of life in children with anorectal malformation (ARM) complicated with spinal cord anomalies (SCA) and analyze the impact of different types of SCA on ARM patients in order to provide a reference for the early clinical identification of high-risk children with poor prognosis. Methods‍　‍A retrospective analysis was conducted on 282 ARM neonates admitted to our department between June 2015 and April 2021. Radiological examinations were applied to evaluate the development of the spinal cord, and Rintala score and the PedsQL 4.0 scale were employed to assess postoperative defecation function and quality of life, respectively. According to their SCA types and other complications, the patients were grouped. The relationship between these factors and defecation function as well as quality of life was then analyzed. Results‍　‍Among the 282 subjected children, 104 (36.9%) had SCA. The incidence of SCA varied significantly across different types of ARM (P=0.002), with the highest incidence observed in vaginal fistula patients (100.0%) and the lowest in children without fistula (13.6%). Radiological findings revealed that sacral bone anomalies were common, with absent coccyx (62.7%) and vertebral anomalies (69.8%) being the most prevalent. The SCA group had significantly lower Rintala bowel function score (12.70±3.24) and PedsQL 4.0 quality of life score (81.42±5.03) than the non-SCA group (P<0.001). As the increment of SCA types, both the Rintala score and PedsQL 4.0 score were in a significant downward trend (P<0.001). Among the children with different types of SCA, those with tethered cord syndrome had the statistically lowest Rintala score (8.05±2.35, P<0.05). Meanwhile, their PedsQL 4.0 score (75.90±3.35) was significantly lower than those of other types except syrinx (P<0.05). Multiple linear regression analysis indicated that both SCA and sacral bone anomalies exerted notably negative impacts on the Rintala score and PedsQL 4.0 score (P≤0.001), with SCA having the most pronounced effect. Conclusion‍　‍SCA is closely associated with postoperative defecation dysfunction and diminished quality of life in ARM children. The greater the type and number of SCAs, the worse the postoperative defecation function and quality of life. Early identification of concomitant SCAs holds significant clinical value for predicting postoperative outcomes in ARM patients.